Supernormalising Nothing from the Hyperbolic Nihil to the Ordinary Supernothing - Ó Maoilearca John (Open Philosophy, 2023)
This essay connects the mystical concept of “supernothing” with Bergson’s notion of the image of nothingness as a movement in the making. I do this also with respect to the film The Empty Man (David Prior, 2020) – which explicitly cites Gorgias’s four-part embargo on nothing (it exists, it cannot be known, communicated, or understood): nothingness is re-rendered as movement, in particular, the transmission and reception of images in the brain. Indeed, this is precisely Bergson’s theory of the brain too – as the receiver and transmitter of images, a communication of movements. This “nihilistic” approach to the brain (it does not store images, it has no positive content) is not a valorisation of the ego as void à la Metzinger, but the real, processual rethinking of what nothingness and nihilism might mean – with a full, moving “supernothing” at its heart. Though there is a mystical and a film-philosophical account referenced in this renewal of nothingness, it will not lead to any exotic or hyperbolic excess (the brain as supernatural agent), but rather a very “ordinary” account that we will describe in terms of “supernormalisation”: an “unlearning” or mundanising of the supernatural: an extraction of the supernatural by natural means.